2020
DOI: 10.3947/ic.2020.52.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Family Physicians' Knowledge about and Attitudes towards COVID-19 - A Cross-sectional Multicentric Study

Abstract: Background:The coronavirus disease 2019 (COVID-19) pandemic has affected every country on earth, and family physicians (FPs) have helped patients at every stage. The first objective of our study was to study the FPs' knowledge about COVID-19 and second objective was to assess their attitudes, stress and death anxiety surrounding the current pandemic. Materials and Methods: An online questionnaire was prepared to collect responses from FPs between March-April 2020. A descriptive and correlational design was uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 30 publications
(35 reference statements)
5
18
2
Order By: Relevance
“…We discovered that there was no significant association between agreeableness and COVID-19 fear, consistent with the findings of Gokdemir et al (2020). The participants in the present study had no COVID-19 fear, which may be because agreeable people are more adaptive compared to other personality types (Ahmed et al, 2021).…”
Section: Discussion Of the Proposed Modelsupporting
confidence: 86%
See 1 more Smart Citation
“…We discovered that there was no significant association between agreeableness and COVID-19 fear, consistent with the findings of Gokdemir et al (2020). The participants in the present study had no COVID-19 fear, which may be because agreeable people are more adaptive compared to other personality types (Ahmed et al, 2021).…”
Section: Discussion Of the Proposed Modelsupporting
confidence: 86%
“…This indicates that conscientiousness is related to individuals' commitment to following the measures for COVID-19 containment. Accordingly, participants who are more conscientious tend to display lower anxiety levels and more constructive attitudes regarding COVID-19 (Gokdemir et al, 2020). Moreover, conscientiousness is an important predictor of intention to quit (Hadiyat et al, 2020); specifically, it is negatively associated with intention to quit (Singh et al, 2014).…”
Section: Impact Of Conscientiousnessmentioning
confidence: 99%
“…There were 25 cross-sectional surveys, 30 33 , 36 50 , 52 , 54 , 55 , 57 59 five qualitative studies, 34 , 35 , 51 , 53 , 56 and one mixed survey and qualitative study. 29 Several validated and some non-validated measures were used to assess outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…A multi-centre study investigating the knowledge and attitudes of 250 family physicians from eight countries about COVID-19 between March and April 2020, in a period that could be considered as the beginning of the pandemic, reported that 105 (42%) participants wanted to volunteer in COVID-19 vaccine studies, and in like manner, 68 (27%) participants stated that they could encourage family members or friends to volunteer (14). In our study, the number of family physicians who voluntarily participated in the Phase 3 Trials of the COVID-19 vaccine was only 6 (1.2%), yet the mean positive attitude score of the participants in relation to their willingness for family members' getting the COVID-19 vaccine was found to be high in all participants with the score of 3.9 ± 0.9.…”
Section: Discussionmentioning
confidence: 99%